Nonlinear Free Vibration of Reinforced Skew Plates with SWCNs Due to Finite Strain (Advances in Applied Mathematics and Mechanics, 2021)
This paper is an attempt to investigate the nonlinear free vibration of skewplates reinforced by carbon nanotubes (CNTs) due to finite strain tensor. The materialproperties of the nano-composite are estimated using the molecular dynamic resultsand the rule of mixture. Also, the differential equations governing the motions arederived on the basis of Classical Plate Theory (CPT) regarding the nonlinear Green-Lagrangestrain tensor. In order to solve the nonlinear equations, Galerkin's method,Frechet derivative and differential quadrature method are used. The effects of volumefraction of functionally graded materials (FGM), skew angle, distribution of CNTs andgeometrical features of the plate on the nonlinear vibration of system have been studied.The results of this study have been compared with other researches and a goodagreement has been achieved.